Answer:
84x¹²
Step-by-step explanation:
To simplify this expression, we work from left to right:
4x(-3x⁸)(-7x³)
Multiplying the coefficients of the first two, we have 4(-3) = -12. Using the laws of exponents, multiplying powers with the same base means we add the exponents; this gives us x(x⁸) = x¹⁺⁸ = x⁹. This gives us
-12x⁹(-7x³)
Multiplying the coefficients, we have -12(-7) = 84. Using the laws of exponents, for the variable we have x⁹(x³) = x⁹⁺³ = x¹²
This gives us
84x¹²
Answer:
i believe the answer is B.432 hope this helps!
Answer:
(x - 2)² + (y - 6)² = 49
Step-by-step explanation:
Equation of a circle formula: (x - a)² + (y - b)² = r²
where (a, b) is the center of the circle and r is the radius
Given, center = (2, 6) and radius = 7
Substitute this information in the equation of a circle formula.
⇒ Equation of the circle: (x - 2)² + (y - 6)² = 49
9514 1404 393
Answer:
- loan: $157,823
- repaid: $378,000
- interest: $220,177
Step-by-step explanation:
For a loan value of 1, the monthly payment on a 30 year loan at 7% is ...
A = (0.07/12)/(1 -(1 +0.07/12)^(-12·30)) ≈ 0.00665302495
Then the amount repaid after 360 payments is ...
360A = 2.39508898 . . . times the principal amount
__
a) For a monthly payment of $1050, the principal can be ...
$1050/0.00665302495 ≈ $157,823
__
b) The amount repaid to the loan company is ...
$157,823×2.39508898 ≈ $378,000
__
c) The amount that is interest is ...
$378,000 -157,823 = $220,177